Parameterizing exercises with Python and LaTeX: a novel strategy for generating teaching and assessment materials in mathematics: Parametrizando ejercicios con Python y LaTeX: una novedosa estrategia para generación de materiales de enseñanza y evaluación en matemáticas - Arroyo Hernández, Jorge (2024)
This article presents a novel approach to teaching by generating exercises from a structured base with pseudorandom parameters. By substituting values with individuals in predetermined ranges, multiple versions of exercises can be obtained. The elements are elaborated and digitized using the Python programming language and its Sympy and Numpy libraries, which automate the generation of exercises, their solutions, and the Latex files. These files can then be compiled massively. One of the main contributions of this development is the creation of personalized lists of elements of similar difficulty, each with feedback for individual students. This approach also saves time in teaching hours.